Peningkatan Kapasitas Pelajar dalam Pencegahan Dini Demam Berdarah Dangue (DBD) Melalui Workshop di SMP Negeri Reroroja - Bura, Bernaditha; Mae, Yohanes Paulus; Rehing, Emilia Yunritati (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Reroroja Village, located in Sikka Regency, is an endemic area with a high number of cases reported annually. Low public awareness of the importance of maintaining environmental cleanliness increases the risk of disease transmission. This Community Service Program (Pengabdian Kepada Masyarakat/PKM) aimed to enhance the ability of students at SMP Negeri Reroroja to conduct early prevention of DHF through interactive training activities. The methods employed included health education using PowerPoint presentations, leaflet distribution, educational games, question-and-answer sessions, and group discussions. The results indicated an improvement in students’ understanding, with 90% of participants able to mention three DHF prevention measures (the 3M Plus movement). Participants’ enthusiasm was evident through their active involvement in asking questions and participating in discussions. This activity demonstrates that school-based education plays an effective role in fostering clean and healthy living behaviors and encouraging students to become agents of change within their communities.